Nutrient Value of Some Lucerne Cultivars Based on Chemical Composition for Livestock - YOLCU, HALIL; DASCI, MAHMUT; TAN, MUSTAFA; COMAKLI, BINALI (Asian Journal of Chemistry, 2010)
This study was carried out to determine of nutrient contents of twelve lucerne cultivars in the highlands of Turkey. There were significant differences (p < 0.01) among the cultivars for crude protein (CP), neutral-detergent fiber (NDF), aciddetergent fiber (ADF), digestible dry matter (DDM), dry matter intake (DMI), relative feed value (RFV), total digestible nutrients (TDN), net energy-lactation (NEl), net energy-maintenance (NEm) and net energy-gain (NEg). Although Planet cultivar had the highest protein content (32.00 %), Kayseri cultivar is one of the lowest protein content (24.17 %) among the all cultivars. Neutral detergent fiber in cultivars ranged from 33.41 % (Seker cultivars) to 50.39 % (Kayseri cultivars). Average acid detergent fiber content for all cultivars was 34.31 %. Relative feed value in cultivars ranged from 104.78 % (Bilensoy-80 cultivars) to 185.03 % (Seker cultivars). The average TDN content was 56.89 %. Evaluating for this respect contents were the most quality Seker, Bilensoy and Savas cultivars among lucerne cultivars. In conclusion, Seker, Bilensoy and Savas cultivars among lucerne cultivars had better nutrient content than other cultivars.